THE EFFECT OF THE USE OF LEARNING RESOURCES AND LEARNING DISCIPLINE ON STUDENT LEARNING ACHIEVEMENT IN BLENDED LEARNING - Rahmanita, Fika (Perspektif Ilmu Pendidikan, 2023)
This study aims to determine the effect of using learning resources and learning discipline on learning achievement in the basics of accounting 1 course in blended learning for Economics Education students at Pamulang University. This study uses a quantitative approach with associative methodology, determining the sample using a sampling technique using a saturated sample technique. Data collection was carried out by observation, interviews, distributing questionnaires and documentation. The data analysis technique used is inferential statistics through pre-requisite tests, namely the normality test, linearity test, multicollinearity test, heteroscedasticity test and autocorrelation test. As well as testing the hypothesis of simple linear regression and multiple linear regression. The results of this study can be concluded that: 1) There is a significant influence between the use of learning resources on learning achievement. 2) There is a significant influence between learning discipline on learning achievement. 3) There is a significant influence between the use of learning resources and learning discipline on learning achievement.